2017
DOI: 10.1038/srep44754
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic effect of pirfenidone in a mouse model of human nonalcoholic steatohepatitis

Abstract: Non-alcoholic steatohepatitis (NASH) is characterized by steatosis with lobular inflammation and hepatocyte injury. Pirfenidone (PFD) is an orally bioavailable pyridone derivative that has been clinically used for the treatment of idiopathic pulmonary fibrosis. However, it remains unknown whether PFD improves liver fibrosis in a mouse model with human NASH-like phenotypes. In this study, we employed melanocortin 4 receptor-deficient (MC4R-KO) mice as a mouse model with human NASH-like phenotypes to elucidate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 49 publications
4
29
0
Order By: Relevance
“…Specifically, PFD was shown to be effective in various in vivo models including a rat model of myocardial infarction [5,6], a mouse model of pulmonary fibrosis [7], a mouse model of nonalcoholic steatohepatitis [8], and a rats model of renal fibrosis [9]. In agreement with in vivo model data, in vitro antiproliferative effects of PFD were also confirmed with human leiomyoma cells [10], human Tenon fibroblasts [11], and rat cardiac fibroblasts [12].…”
Section: Introductionsupporting
confidence: 68%
“…Specifically, PFD was shown to be effective in various in vivo models including a rat model of myocardial infarction [5,6], a mouse model of pulmonary fibrosis [7], a mouse model of nonalcoholic steatohepatitis [8], and a rats model of renal fibrosis [9]. In agreement with in vivo model data, in vitro antiproliferative effects of PFD were also confirmed with human leiomyoma cells [10], human Tenon fibroblasts [11], and rat cardiac fibroblasts [12].…”
Section: Introductionsupporting
confidence: 68%
“…In a recent study reported by Zou et al, pirfenidone was found to promote apoptosis in hepatocellular carcinoma cells, which was confirmed by Western blot analysis [53]. In another study by Komiya et al, it was reported that PFD could be repurposed for human non-alcoholic steatohepatitis [72].…”
Section: Discussionmentioning
confidence: 74%
“…Second, Komiya et al measured these metabolic sensors only at the mRNA level. (15) It has been described previously that most molecules involved in hepatic lipolytic processes can be regulated at different gene-expression levels, not only the transcriptional one. (26) Therefore, we examined the hepatic tissue key enzymes and upstream effectors in lipid metabolism at the protein level, using western blot and immunofluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…Third, another explanation for this discrepancy is that Komiya et al used MC4R-KO mice, rodents with no membrane-bound receptor of the melanocortin receptor family associated with autosomal dominant obesity. (15) Such a mice model would strictly resemble a genetic morbid disease that causes obesity since the neonatal stages. (27) They did not observe differences by regular PFD treatment in mRNA levels of molecules implicated in lipid metabolism, probably due to the fact that genetic predisposition to obesity is present since birth in these animals and could be masking differences in fat metabolism.…”
Section: Discussionmentioning
confidence: 99%